BIOLOGICS BEFORE SURGERY FOR IBD: ARE THEY ASSOCIATED WITH POST-OPERATIVE INFECTIOUS COMPLICATIONS? RESULTS FROM THE NATIONAL SURGICAL QUALITY IMPROVEMENT PROGRAM INFLAMMATORY BOWEL DISEASE COLLABORATIVE IN >1500 PATIENTS. (21st January 2021) - Holubar, Stefan; Eisenstein, Samuel; Bordeianou, Liliana; Jia, Xue; Hull, Tracy; Hyman, Neil; Lee, Edward; Messaris, Evangelos; Ramamoorthy, Sonia; Saraidaridis, Julia; Scow, Jeffrey; Shaffer, Virginia; et al.
Abstract: Background: We aimed to utilize the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) Inflammatory Bowel Disease (IBD) Collaborative, which includes disease-specific variables, to assess the association between preoperative biologic exposure and post-operative infectious complications in the largest cohort reported to date. Methods: Data was obtained from ten IBD centers from 2017 - 2018. Univariate and multivariate analyses were performed, with any biologic use within 60-days of surgery as the primary predictor, adjusting for diagnosis, chronic steroid use, immunomodulator (IMM) use, ostomy construction, anemia, malnutrition, operative length, emergency surgery, and other variables with p<0.05 from the univariate analysis. The primary endpoint was any (composite) infectious complication, and the secondary endpoint was any (composite) surgical site infection. Results: A total of 1, 562 patients were included, of which 832 (53%) were not exposed to biologics, and 730 (47%) were exposed to biologics before surgery. The biologics group had more preoperative weight loss, lower albumin, more systemic sepsis, more IMM and steroid use, and more had Crohn's disease (all p<0.001). The biologics group were also more likely to receive a new ostomy and to have a colectomy (vs. proctectomy or small bowel procedure), and fewer had elective surgery (all p<0.001). On univariate analysis (Table 1 ), compared with no biologic exposure, biologic exposure was not associated with any infectious complications, any surgical site infections, anastomotic leak after colectomy, or other post-operative outcomes, but was associated with increased rate of anastomotic leak after proctectomy (n=423), 6.7% vs. 1.9%, p=0.02. With respect to the primary and secondary outcomes, the results of the multivariate analyses are shown in Table 2 . Biologics were shown not to be associated with any infectious complication (OR 0.88, 95%CI 0.54 – 1.42) or any surgical site infection (OR 0.77, 95% CI 0.46 – 1.28), while Crohn's disease was associated with any infectious complications (OR 2.11 95% CI 1.12 – 4, p=0.02). Conclusions: In the largest nationally representative retrospective cohort to date, we found that biologics exposure within 60-days of surgery for IBD, using well-validated methodology and after vigorous adjustment for disease- and surgery-specific covariates, was not associated with post-operative infectious or surgical site infectious complications.